2019
DOI: 10.3390/molecules24234266
|View full text |Cite
|
Sign up to set email alerts
|

Novel Convenient Approach to the Solid-Phase Synthesis of Oligonucleotide Conjugates

Abstract: A novel and convenient approach for the solid-phase 5′-functionalization of oligonucleotides is proposed in this article. The approach is based on the activation of free 5′-hydroxyl of polymer support-bound protected oligonucleotides by N,N′-disuccinimidyl carbonate followed by interaction with amino-containing ligands. Novel amino-containing derivatives of closo-dodecaborate, estrone, cholesterol, and α-tocopherol were specially prepared. A wide range of oligonucleotide conjugates bearing closo-dodecaborate, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 46 publications
0
24
0
Order By: Relevance
“…The synthesis of 3'-alkyne derivatives of oligonucleotides was performed using modified polymer support 3'-alkyne-Modifier Serinol CPG for solid-phase phosphoramidite synthesis. For 5'-alkyne derivatives, we employed the previously described by us method [10] based on the activation of a 5'-hydroxy group of protected support-bound oligonucleotide by N,N'-disuccinimidyl carbonate (DSC) followed by the interaction with propargylamine. The series of alkyne-modified oligomers included 3'-, 5'-and dual 3',5'-modified oligodeoxyribonucleotides, oligoribonucleotides, oligo(2'-O-methylribonucleotides), and oligoribonucleotides with all pyrimidine nucleotides replaced by their 2'-fluoro analogs.…”
Section: Synthesis Of 5'-and/or 3'-alkyne-modified Oligonucleotidesmentioning
confidence: 99%
See 2 more Smart Citations
“…The synthesis of 3'-alkyne derivatives of oligonucleotides was performed using modified polymer support 3'-alkyne-Modifier Serinol CPG for solid-phase phosphoramidite synthesis. For 5'-alkyne derivatives, we employed the previously described by us method [10] based on the activation of a 5'-hydroxy group of protected support-bound oligonucleotide by N,N'-disuccinimidyl carbonate (DSC) followed by the interaction with propargylamine. The series of alkyne-modified oligomers included 3'-, 5'-and dual 3',5'-modified oligodeoxyribonucleotides, oligoribonucleotides, oligo(2'-O-methylribonucleotides), and oligoribonucleotides with all pyrimidine nucleotides replaced by their 2'-fluoro analogs.…”
Section: Synthesis Of 5'-and/or 3'-alkyne-modified Oligonucleotidesmentioning
confidence: 99%
“…Oligonucleotides bearing a 3'-alkyne group were synthesized using modified polymer support 3'-alkyne-Modifier Serinol CPG (Glen Research, USA). Oligonucleotides with 5'-alkyne modification were obtained in analogy with [10] (see Supplementary for more details). After synthesis, cleavage from support and deprotection of the oligonucleotides were carried out with 300 μL of 40% aq.…”
Section: Synthesis Of Oligonucleotidesmentioning
confidence: 99%
See 1 more Smart Citation
“…Meschaninova et al [45] stated a novel synthesis of oligonucleotide conjugates through solid-phase synthesis based on the interaction of free 5-hydroxyl oligonucleotides and amino-containing ligands such as closo-dodecaborate, oestrone, cholesterol and alphatocopherol. Initially, functionalization of 5-hydroxyl oligonucleotides catalysed by N,N-disuccinimidyl carbonate followed by interaction with an amino group-containing ligand which led to the formation of a wide range of oligonucleotide conjugates such as closo-dodecaborate, lipophilic residues, aliphatic diamines, pyrene, short peptide and propargylamine.…”
Section: Synthesis Of Organic Compoundsmentioning
confidence: 99%
“…DSC is widely used to produce modified polymer surfaces and to introduce PEG to the definite sites of proteins or nucleic acids. The advantages of DSC are a longer lifespan, wide range of suitable solvents and higher reactivity towards the activated hydroxyl groups [ 27 ]. Several studies have shown that DSC-mediated amination techniques provide higher coupling yields [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%